Acceptability of artificial intelligence in inclusive education: a TAM2-based study among preservice teachers - Amouri, Houda; Haroud, Samia; Ouchaouka, Lynda; Saqri, Nadia (Frontiers in Artificial Intelligence, 2025)
IntroductionThe integration of artificial intelligence (AI) into education is generating growing interest, particularly due to its potential to support inclusive pedagogical practices. This is especially relevant for addressing the needs of students with attention deficit hyperactivity disorder (ADHD). The success of such integration largely depends on the acceptability of AI tools by educators, especially those still in initial training. This study aims to identify the factors influencing the acceptability of AI among pre-service teachers in the specific context of teaching students with ADHD.MethodsGrounded in the Technology Acceptance Model 2 (TAM 2), the study adopts a mixed-methods approach. Quantitative data were collected via structured questionnaires, and qualitative insights were obtained through semi-structured interviews with pre-service teachers in Morocco.ResultsFindings reveal that perceived usefulness is the most influential predictor of AI acceptability, followed by perceived ease of use, voluntariness, and subjective norms. Participants emphasized the potential of AI to enhance pedagogical efficiency and support differentiated instruction. Institutional support and interface simplicity also emerged as key enablers.Discussion/ConclusionThese results highlight the need to incorporate digital literacy into teacher training programs and to develop AI tools specifically adapted to students with special educational needs. They also call for the establishment of a robust ethical and regulatory framework to ensure the responsible, equitable, and secure use of AI in education.